Specific cultural values affect basic political activities in Vietnam - Nguyễn Thị Hồng Minh; Cường Nguyễn Anh (Cogent Social Sciences)
The empirical analysis determines how cultural values affect fundamental political activities. Political participation and governance activities have two main components. Policy consultation and authorization are the first steps in political participation. It means people can voice their opinions and provide input on government policies and decisions. Second, governance activities are government actions to manage public affairs. Public administration includes staff selection, collective decision-making, and central-local government relations. The article examines how community, hierarchical order, and harmony, three core values of Vietnamese culture, affect non-political people. It can make it difficult for the government to understand and meet citizens’ needs. Additionally, many factors affect public governance. These include the importance of consensus in collective decision-making, age, ethnicity, and compatriotism in selecting officials. These factors coexist with two governance institutions: the ‘village’ and the ‘country’. The article concludes that while cultural values may change in order and priority, Vietnam’s culture remains community-focused. Hierarchy and harmony are more important than equality and competition. These values strongly influence Vietnam’s politics.